Peran Kewirausahaan Dalam Memajukan Perekonomian Bangsa - Amelia Sekar Ayu Pramesti; Dara Kesumadewi; Zona Oktavia; Nur Fitriana (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2024)
This research aims to give stakeholders access to assessment resources so that entrepreneurship can provide the best thing for the progress of the nation's economy. This type of research is descriptive qualitative with a literature study approach. The data collection technique used by the author in this research is a literature study taken from google scholar. The results of this study indicate that entrepreneurship plays a role in encouraging the economic activities of families, communities, companies, and countries. The dynamics of these business activities can encourage economic growth and improve people's welfare. The number of entrepreneurs in Indonesia is still small compared to the population so efforts to increase entrepreneurship must continue. Empirical evidence indicates that entrepreneurs significantly contribute to enhancing the standard of living of people, communities, and nations. Another factor that determines the development of a rich nation and society is entrepreneurship.